Planning for the Development of the Meranti Bay Bono Wave Surfing Sport - Yani, Ahmad; Henjilito, Raffly (Indonesian Journal of Sport Management, 2024)
This research aims to determine the planning for developing Meranti Bay's bono wave surfing sport. This study was carried out using a qualitative descriptive approach. Data collection techniques include observation, interviews, and participant documentation. The data analysis is carried out through data analysis, data presentation, and drawing conclusions/verification. Based on the research results and discussion of the focus of the problem in this research, several conclusions can be drawn: Firstly, planning to develop Meranti Bay surfing sports has involved many other related stakeholders. The stages of planning for the development of surfing sports in Bono tourist destinations are 1) preparation of initial needs, 2) study of potential development studies and tourism programs, 3) preparation of human resources, 4) strengthening of institutions, 5) preparation of infrastructure and facilities, 6) Preparation of programs, 7) socialization, 8) implementation and implementation of activities, 9) monitoring and evaluation. Generally, it can be divided into three stages: decision/policy making, planning and implementation processes. The two factors that influence planning for the development of surfing in Bono tourist destinations are human resource factors, environmental factors, potential factors, funding and budget factors.